PERAN GURU PROFESIONAL DALAM MELATIH KEMAMPUAN AKADEMIK PESERTA DIDIK - Ali Mahsun; Rizqi Damayanti (IKIP PGRI Jember, 2017)
This research is qualitative field with case study approach. The presence of researchers is one important element because of the presence and involvement of researchers in the field for planners, implementing data collection, analysis, interpretation of data. Techniques of collecting data using interviews, observation and documentation. Data analysis techniques use domain analysis. hecking the validity of data, credibility, observational persistence, and triangulation. The role of professional teachers in training students' academic ability at MIN Pucangsimo is by improving the quality of learning by applying PAKEM learning, combining active learning methods and models to create an active and fun learning atmosphere. Hold a special study program. Instill and familiarize discipline from an early age in the school. Directing learners to develop their abilities through extracurricular activities in MIN Pucangsimo.